Altered expression of NEAT1 variants and P53, PTEN, and BCL-2 genes in patients with acute myeloid leukemia. (April 2022) - Rostami, Mehrdad; kharajo, Ramin Saadatian; Parsa-kondelaji, Mohammad; Ayatollahi, Hossein; Sheikhi, Maryam; Keramati, Mohammad Reza
Abstract: Background: Newly discovered evidence showed that long non-coding RNAs (lncRNAs) can play crucial roles in the development of cancer therapies. Nuclear Enriched Abundant Transcripts 1 ( NEAT1 ) is one of the lncRNAs the expression of which changes in different cancers. The role of NEAT1 in apoptosis is discussed in various malignancies. This study aimed to determine the NEAT1 expression and its correlation with P53, PTEN, and BCL-2 genes expression in acute myeloid leukemia (AML) patients. Method: In this study, using quantitative real-time polymerase chain reaction (qRT-PCR), we analyzed the expression of NEAT1, P53, PTEN, and BCL-2 genes in 21 AML patients. Moreover, relative quantification analysis was performed by delta-delta CT method (2 −ΔΔCT) method. Results: Our results showed that NEAT1 expression was significantly lower in AML patients compared to healthy controls ( P-value  < 0.05). While a significant correlation was observed between the expression levels of NEAT1 and PTEN genes in AML patients ( P-value  < 0.05), there was no correlation between the expression levels of NEAT1 with P53 and BCL-2 ( P-value  > 0.05). Conclusion: According to the results, increased expression of NEAT1 gene may play a role in the apoptosis of AML cells, despite the oncogenic role in most solid tumors. Highlights: Expression of the NEAT1 variants decreases in patients with Acute Myeloid Leukemia (AML). The expression of PTEN and P53 genes is reduced in AML patients. BCL-2 gene expression is increased in patients with AML. NEAT1 expression is correlated to PTEN expression.